Cytokines possibly involved in idiopathic epiretinal membrane progression after uncomplicated cataract surgery. (April 2022) - Song, Pei; Li, Pengfei; Geng, Wenjing; Qin, Miaomiao; Su, Shu; Zhou, Tianqiu; Yuan, Yurong; Zhang, Guowei; Wu, Jian; Ji, Min; Guan, Huaijin
Abstract: Epiretinal membrane (ERM) is a common retinal fibrotic disorder disease causing visual impairment and metamorphopsia. Recently, increasing attention has been devoted to ERM progression after uncomplicated cataract surgery. Cytokines, which play a role in diverse physiological and pathological activities in eyes, are suggested to be involved in these postoperative changes. However, few studies have investigated the post-cataract surgery cytokine expression changes in ERM eyes and their roles in the postoperative changes. The purpose of this study was to evaluate the aqueous levels of cytokines in eyes with idiopathic epiretinal membrane (iERM) both pre- and post-cataract surgery, and their correlations with postoperative iERM progression. In this study, aqueous humor (AH) samples were collected from iERM eyes (n = 25) and non-iERM eyes (n = 23) from 48 patients (48 eyes) undergoing uncomplicated cataract surgery preoperatively and 20 h postoperatively. Samples were analyzed for 48 cytokines with multiplex bead-based immunoassay. Correlations between cytokine level changes (postoperation vs. preoperation) and three-month postoperative best-corrected visual acuity (BCVA) and optical coherence tomography measure changes were evaluated in iERM eyes. We found that in iERM eyes, the levels of 4 cytokines exhibited significant elevations when compared with those in the controls (all p ≤ 0.0015) preoperatively. Postoperatively, the concentrations of 21 cytokines were higher than the preoperative levels in iERM eyes (all p ≤ 0.0015), among which GRO-α, IL-8, and MCP-3 levels showed more pronounced changes than the controls. Additionally, in iERM eyes, IL-4 level changes showed moderate positive correlations with MV (r = 0.492, p = 0.028) and MT (r = 0.481, p = 0.032) changes. LogMAR changes were positively correlated with IL-1α (r = 0.553, p = 0.011), IL-12(P40) (r = 0.544, p = 0.013), and MCP-3 (r = 0.588, p = 0.006) level changes. No significant cytokine-level-change differences were found between eyes with and without postoperative cystoid macular edema development. In conclusion, cataract surgery will bring great alterations to the specific intraocular cytokine microenvironment inherently in eyes with iERM. Many fibrotic and inflammatory cytokines showing elevated levels or relationships with clinical characteristics are suggested to be involved in the pathogenesis and post-cataract surgery progression of iERM; however, further investigations are needed to discern their real roles. Highlights: IERM eyes have unique aqueous cytokine environment pre- and post-cataract-surgery. GRO-α, IL-2, IL-7, and PDGF-BB may take part in the pathogenesis of iERM. Eyes with iERM exhibit worse recovery outcomes post cataract surgery. New cytokines are found involved in the post-cataract-surgery development of iERM.